Yeats and theosophy - Monteith, Ken (Studies in major literary authors (Unnumbered), 2008)
When H.P. Blavatsky, the controversial head of the turn of the century movement Theosophy, defined ""a true Theosophist"" in her book The Key to Theosophy, she could have just as easily have been describing W.B. Yeats. Blavatsky writes, ""A true Theosophist must put in practice the loftiest moral ideal, must strive to realize his unity with the whole of humanity, and work ceaselessly for others."" Although Yeats joined Blavatsky's group in 1887, and subsequently left to help form The Golden Dawn in 1890, Yeats's career as poet and politician were very much in line with the methods set for.